2008
DOI: 10.1007/978-1-60327-159-2_16
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Model Evaluation

Abstract: Most phylogenetic methods are model-based and depend on Markov models designed to approximate the evolutionary rates between nucleotides or amino acids. When Markov models are selected for analysis of alignments of these characters, it is assumed that they are close approximations of the evolutionary processes that gave rise to the data. A variety of methods have been developed for estimating the fit of Markov models, and some of these methods are now frequently used for the selection of Markov models. In a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
45
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 122 publications
5
45
0
Order By: Relevance
“…Evidence of evolution under conditions more complex than that assumed by commonly applied models (i.e., stationary, reversible, and homogeneous conditions) was inferred if the scatter of dots in the tetrahedral plots was widely dispersed and if x% of the matched-pairs tests of symmetry produced p values greater than or equal to x; this procedure is consistent with that advocated by Jermiin et al (2008). Substitution saturation was tested by inspecting a new entropy-based index as implemented in DAMBE (Xia and Xie 2001).…”
Section: Sequence Alignment and Analysessupporting
confidence: 63%
“…Evidence of evolution under conditions more complex than that assumed by commonly applied models (i.e., stationary, reversible, and homogeneous conditions) was inferred if the scatter of dots in the tetrahedral plots was widely dispersed and if x% of the matched-pairs tests of symmetry produced p values greater than or equal to x; this procedure is consistent with that advocated by Jermiin et al (2008). Substitution saturation was tested by inspecting a new entropy-based index as implemented in DAMBE (Xia and Xie 2001).…”
Section: Sequence Alignment and Analysessupporting
confidence: 63%
“…Kim et al (1994) a Inferred from ITS1 sequence analysis (Yang et al 2010) b Named previously on the basis of zymodeme analysis (Xu et al 1984) c Identified as L. donovani according to the zymodeme, LON41, whereas recent analysis have shown that it is L. infantum (Ibrahim and Barker 2001) Compositional heterogeneity was evaluated using Chisquare (# 2 ) tests implemented in PAUP* 4.0b10 (Swofford 2002) and assessed using the software SeqVis v.1.5 (Ho et al 2006) to visualize and to conduct matched-pairs test of symmetry (Ababneh et al 2006). Evidence of evolution under conditions more complex than that assumed by commonly applied models (i.e., stationary, reversible, and homogeneous conditions) was inferred if the scatter of dots in the tetrahedral plots was widely dispersed and if x% of the matched-pairs test of symmetry produced p values greater than or equal to x; this procedure is consistent with that advocated by Jermiin et al (2008). Substitution saturation was tested by inspecting a new entropy-based index as implemented in DAMBE v.5.2.11 (Xia and Xie 2001).…”
Section: Sequence Alignment and Analysessupporting
confidence: 52%
“…Evidence of evolution under conditions more complex than that assumed by commonly applied models (i. e., stationary, reversible and homogeneous conditions) was inferred if the scatter of dots in the tetrahedral plots was widely dispersed and if a proportion X of the matched-pairs tests of symmetry rejected symmetry with P-values less than or equal to X. This procedure is consistent with that advocated by Jermiin et al (2008Jermiin et al ( , 2009. If the matched-pairs tests yield a larger than expected proportion of probabilities ≤ 0.05 (i. e., with > 5% of the tests producing probabilities ≤ 0.05), then the conclusion is that the sequences have not evolved under stationary, reversible and homogeneous conditions.…”
Section: Sequence Alignment and Analysessupporting
confidence: 67%